Analisis Perbandingan Semantik Partikel Mi, Ji, dan Pi dalam Teks Media Sosial Syakira Ainun - Zariat Zariat; Munirah Munirah; Anin Asnidar (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the semantic functions of the regional particles mi, ji, and pi in social media communication within South Sulawesi. These particles frequently appear in posts, comments, and informal conversations across digital platforms such as Instagram, X (formerly Twitter), and TikTok. The research employs a qualitative approach using a descriptive-analytical method. Data were collected through documentation techniques by compiling user posts and comments that actively utilized these particles. The analysis was conducted interpretively to identify the meanings, semantic roles, and pragmatic aspects associated with the usage of each particle. The findings reveal that mi, ji, and pi serve various semantic functions, including assertion, emotional marking, and meaning reinforcement. These particles do not merely function grammatically; they also carry social and cultural significance, reflecting the speaker’s identity, particularly among communities in South Sulawesi. The use of these particles is strongly influenced by the user’s social context, interpersonal relationships, and the informal, community-based nature of digital communication. In the realm of social media, these elements enhance personal expression and foster a sense of belonging among users who share similar cultural backgrounds. This study highlights the importance of understanding regional language dynamics within the context of modern digital communication. Therefore, further research is recommended, particularly in the areas of pragmatics, sociolinguistics, and cross-platform language use, to deepen insights into how local languages adapt to and function in contemporary discourse. Moreover, integrating knowledge about these particles into language education and the development of digital learning materials is encouraged. Such efforts could contribute to preserving local languages while simultaneously improving linguistic literacy among the public—especially the younger generation—in today’s digital era. This not only promotes cultural recognition but also reinforces the value of indigenous linguistic identity in the evolving landscape of online communication.